CURRENT ISSUES OF ENSURING THE PSYCHOLOGICAL SAFETY OF STUDENTS IN HIGHER EDUCATIONAL INSTITUTIONS (Universal International Scientific Journal, 2026)
This thesis examines the current issues of ensuring the psychological safety of students in higher education institutions. The study analyzes the stress factors of students, adaptation processes, and pedagogical and psychological measures to support their mental health [1]. The results of the study show that strengthening psychological safety in universities, creating a supportive environment, and implementing stress-reducing programs can improve students' mental health and academic performance.
Keywords: psychological safety of students, higher education, stress, adaptation, mental health, pedagogical support